Herlyn–Werner–Wunderlich syndrome: An "early" onset case report and review of Literature. (2015) - Angotti, R.; Molinaro, F.; Bulotta, A.L.; Bindi, E.; Cerchia, E.; Sica, M.; Messina, M.
Highlights: We describe a case of a 3 years old girl, with all features of Herlyn–Werner–Wunderlich syndrome (HWWS) who came to our attention for lower abdominal mass. Only six cases are reported in Literature with early onset of this syndrome under 5 years. The aim of this article is to share our experience and focus the attention on the importance of high level of suspicion of HWWS in neonatal period to early diagnosis and treatment. The possible early presentation of this syndrome should be suspected in all neonates (females) with renal agenesia confirmed postnatally or with prenatal diagnosis. An error of evaluation with planning of removal of mass, that can damage patients in term of chance for a successful reproductive outcome. Our team consider HWWS as differential diagnosis in newborn with prenatal ultrasonography of a cystic mass behind the urinary bladder in the absence of a kidney and plan a pelvic ultrasound (with aim to identify an uterus, normal or dydhelfus, and presence or absence of pelvic mass), an examination under anesthesia and cisto-vaginoscopy, if it is necessary. A high level of suspicion, indeed, is the key to early diagnosis. Abstract: Herlyn–Werner–Wunderlich syndrome (HWWS) is a rare congenital mullerian anomaly consisting of uterus didelphys, hemivaginal septum, and unilateral renal agenesis[1, 2] . Most authors reported cases of Herlyn–Werner–Wunderlich syndrome with prepuberal or postpuberal onset with cyclical abdominal pain and a vaginal mass (3–8). Only six cases are reported in Literature with early onset of this syndrome under 5 years (9–14). Our case is about 3 years old girl, with all the features of this syndrome who came to our attention for lower abdominal mass. The aim of this article is to share our experience and focus the attention on the importance of high level of suspicion of HWWS in neonatal period to early diagnosis and treatment. The possible early presentation of this syndrome should be suspected in all neonates (females) with renal agenesia confirmed postnatally or with prenatal diagnosis. It is common, in fact, an error of evaluation with planning of removal of mass, that can damage patients in term of chance for a successful reproductive outcome. For all these reasons, our team consider HWWS as differential diagnosis in newborn with prenatal ultrasonography of a cystic mass behind the urinary bladder in the absence of a kidney and plan a pelvic ultrasound (with aim to identify an uterus, normal or dydhelfus, and presence or absence of pelvic mass), an examination under anesthesia and cystoscopy and vaginoscopy, if it is necessary. A high level of suspicion, indeed, is the key to early diagnosis.